Late Quaternary Dust, Loess and Desert Dynamics in Upwind Areas of the Chinese Loess Plateau - Qiang, Mingrui; Stevens, Thomas; Li, Guoqiang; Hu, Ling; Wang, Xiaowei; Lang, Wenzhe; Chen, Jie (Frontiers in Earth Science, 2021)
As a key global climate and dust archive, the nature of Chinese loess generation, transport and deposition remains debated. The lack of consensus on dust dynamics from sources to leeward regions fundamentally limits interpretation of the preserved past climate and dust record. Here, we investigate chronostratigraphic variability of aeolian deposits in upwind regions of the modern Chinese Loess Plateau (CLP) and attempt to understand dust dynamics that potentially affects loess deposition downwind. The strata consist of alternating layers of typical loess, well-sorted sand, and sandy loess, with obvious unconformities occurring at the transitions from loess to sand. We suggest that pre-existing typical loess in regions to the northwest of the modern CLP was eroded by wind, providing a significant source of homogeneous dust for the dust deposits downwind. The sand deposits interbedded with typical loess at the study sites suggests that proximal deserts have greatly expanded and contracted repeatedly prior to the Holocene. However, the spatial extents of the deserts, as inferred from the sections here, have not markedly diminished after the major expansion during the Last Glacial Maximum. Such a pattern of proximal desert dynamics plays an important role in regulating dust emission and transport, strongly affecting dust sequences on the CLP. Our results suggest a complex scenario of dust dynamics in upwind regions of the CLP at least over the Late Quaternary; the involved processes have to be considered when using conventional proxies from Chinese loess deposits to recover the history of climate and dust changes.